"Inside‐Out" Central Venous Access approach with infraclavicular exit for right‐sided CRT‐D Implantation in bilateral brachiocephalic and superior vena cava occlusion. Issue 6 (4th April 2021) - Tonko, Johanna B.; Black, Stephen A.; Rinaldi, Christopher A.
Abstract: The use of the "inside‐out" approach with an infraclavicular exit site with a dedicated system in the presence of complex central venous occlusion is feasible and safe for the implantation of complex cardiac devices. Abstract : The use of the "inside‐out" approach with an infraclavicular exit site with a dedicated system in the presence of complex central venous occlusion is feasible and safe for the implantation of complex cardiac devices.